The Impact of the COVID-19 Pandemic at the Makassar Shipping Science Polytechnic - Supardi Supardi; Andi Agustang (JED (Jurnal Etika Demokrasi), 2022)
The spread of COVID-19 is a threat to humanity because this pandemic has forced many global activities to close, including educational activities. To reduce the spread of the virus, educational institutions are forced to turn to e-learning using available educational platforms, despite the challenges that challenge this transformation. To further explore the potential challenges faced by learning activities, this study focuses on e-learning from the perspective of cadets and teachers in using and implementing e-learning systems in universities during the COVID-19 pandemic. This research targets the community, including cadets and teaching staff at the Engineering Study Program at the Makassar Marine Science Polytechnic. A descriptive-analytical approach was applied, and statistical methods analyzed the results. There are two types of questionnaires designed and distributed: student questionnaires and teacher questionnaires. Four dimensions have been highlighted to achieve the expected results: the extent to which e-learning is used during the COVID-19 pandemic, the advantages, disadvantages, and application of E-learning at the Makassar Shipping Science Polytechnic. By analyzing the results, we achieved an exciting result using some of the problems, challenges and advantages of using an e-learning system over traditional education in higher education in general and during times of emergency.Penyebaran COVID-19 menjadi ancaman bagi umat manusia, karena pandemi ini memaksa banyak kegiatan global ditutup, termasuk kegiatan pendidikan. Untuk mengurangi penyebaran virus, institusi pendidikan terpaksa beralih ke e-learning menggunakan platform pendidikan yang tersedia, meskipun ada tantangan yang dihadapi transformasi mendadak ini. Untuk lebih mendalami potensi tantangan yang dihadapi kegiatan pembelajaran, fokus kajian ini adalah pada e-learning dari perspektif taruna dan pengajar dalam menggunakan dan mengimplementasikan sistem e-learning di politeknik negeri selama masa pandemi COVID-19. Penelitian ini menyasar masyarakat yang meliputi taruna dan staf pengajar pada Program Studi Teknika di Politeknik Ilmu Pelayaran Makassar. Pendekatan deskriptif-analitis diterapkan dan hasilnya dianalisis dengan metode statistik. Ada dua jenis angket yang dirancang dan disebarkan, yaitu angket siswa dan angket pengajar. Empat dimensi telah disorot untuk mencapai hasil yang diharapkan, yaitu sejauh mana penggunaan e-learning selama pandemi COVID-19, kelebihan, kekurangan dan hambatan penerapan E-learning di Politeknik Ilmu Pelayaran Makassar. Dengan menganalisis hasil, kami mencapai hasil yang menggembirakan yang menyoroti beberapa masalah, tantangan, dan keuntungan menggunakan sistem e-learning daripada pendidikan tradisional di pendidikan tinggi pada umumnya dan selama masa darurat.